ICD-11 Personality Disorders: Utility and Implications of the New Model - Mulder, Roger T. (Frontiers in Psychiatry, 2021)
The ICD-11 classification of personality disorders represents a paradigm shift in diagnosis. This was felt necessary because previous personality disorder classifications had major problems. These included unnecessary complexity, inconsistency with data on normal personality traits, and minimal consideration of severity despite this being shown to be the major predictor of outcome. The ICD-11 classification abolishes all categories of personality disorder except for a general description of personality disorder. This diagnosis can be further specified as ‘mild’, ‘moderate’ or ‘severe’. Patient behaviour can be described using one or more of five personality trait domains; negative affectivity, dissociality, anankastia, detachment, and disinhibition. Clinicians may also specify a borderline pattern qualifier. The ICD-11 shows considerable alignment with the DSM-5 Alternative Model for Personality Disorders. Early evidence around the reliability and validity of the new model appear promising, although at present there is still limited specific evidence due to the model being so recently finalised. However, for the model to be successful, it needs to be embraced by clinicians and used widely in normal clinical practice.